Elena Garro sin censura, de Patricia Rosas Lopátegui - DePaoli, Maria Teresa (Imagofagia, 2024)
Sobre Rosas Lopátegui, Patricia. Elena Garro sin Censura. México: Gedisa, 2023. 807 pp. ISBN: 978-607-8866-56-4.